Engaging the Past: Charles M. Goethe, American Eugenics, and Sacramento State University - Platt, Anthony M. (Social justice, 2005)
Part of a special issue on the many faces of violence. In 1936, Charles M. Goethe, widely respected philanthropist and benefactor of California State University in Sacramanto, gave a presidential address to the Eugenics Research Association that defended Nazi Germany's use of eugenics. The case of Goethe offers insights into the difficulties faced by universities confronting institutional legacies of hatred. When the university, then Sacramento State College, was courting Goethe for his money and prestige in the late 1940s to the early 1960s, it turned a blind eye to his widely known racist opinions. However, once his bigotry became a public embarrassment, the institution distanced itself from Goethe while continuing to use his bequest.